In vivo histomorphological evaluation of geopolymer-carbonated apatite nanocomposites implanted on rabbit tibia at early bone healing - Sutanto, Dahlia; Satari, Mieke Hemiawati; Hernowo, Bethy Suryawathy; Priosoeryanto, Bambang Pontjo; Septawendar, Rifki; Asri, Lia Amelia Tresna Wulan; Purwasasmita, Bambang Sunendar (Padjadjaran Journal of Dentistry, 2021)
Introduction: Dental implants have become a more desirable treatment for replacing missing teeth. The mechanical properties and biocompatibility of titanium and zirconia are excellent, but they are less bioactive. The chemical composition of the carbonate apatite is similar to enamel and dentin. Geopolymers are inorganic polymers, and they are similar to ceramics. They have excellent mechanical properties, bioactivity, biocompatibility. The purpose of this study was to assess histomorphological evaluation of geopolymer-carbonated apatite nanocomposites implanted on rabbit tibia at early bone healing in vivo. Methods: Geopolymer-CHA nanocomposites with a diameter of 3 mm and length of 6 mm was placed in the tibia of eight male New Zealand White rabbit whose body weight is 3 to 3.5 kg and six-month ages. Experimental subjects were randomly assigned to 2 groups for assessing the bone healing capability around samples to 14 and 28 days histomorphologically. Wilcoxon test was performed, and p<0.05 was considered significant, using Minitab software version 13. Results: Granulation tissue, woven, and lamellar bone was analysed. A reactive bone formation was revealed in the 14th day. Osteoblasts, osteoids, and osteocytes showed more mature and woven bone became denser on the 28th day. Conclusion: Geopolymer-CHA nanocomposites could be considered a candidate for dental implant material from this histomorphological evaluation.